Sisteme de valori și participare politică - Manea, Livius (Calitatea Vieții, 1991)
Owing to the rapid political, economic and social changes, the present-day systems of values undergo the phenomenon of crisis, not being able to act as adjustable factors of the social action and to meet a minimum degree of social coherence and cohesion, the political values aim to be established as central elements of the new systems of values, but this process seems to be a difficult and a long lasting one, closely linked to the process of political socialization.